Effects of short-term ambient air pollution exposure on HPV infections: A five-year hospital-based study. (August 2020) - Liang, Zhen; Xu, Chen; Ji, Ai-Ling; Liang, Shi; Kan, Hai-Dong; Chen, Ren-Jie; Lei, Jie; Li, Ya-Fei; Liang, Zhi-Qing; Cai, Tong-Jian
Abstract: Human papillomavirus (HPV) infections are common sexually-transmitted diseases among reproductive-aged women with increasing concern. Until now, there are no prior study about the association between HPV infections and ambient air pollution. This study aimed to explore the relationship between short-term exposure to ambient pollutants and daily outpatient visits for HPV infections in China. Data of daily outpatient visits for HPV infections were obtained from January 1, 2014 to December 31, 2018 (1826 days). Over-dispersed Poisson generalized additive models were applied by adjusting weather conditions and day of the week. We identified a total of 39, 746 cases for HPV infections. A 10 μg/m 3 increase of PM10, PM2.5, SO2, and NO2 or a 0.1 mg/m 3 rise of CO in concurrent day (lag 0) concentrations was related to an elevation of 0.822% (95% Cl: 0.282%, 1.36%), 1.05% (95% Cl: 0.280%, 1.81%), 5.72% (95% Cl: 1.79%, 9.65%), 5.02% (95% Cl: 3.45%, 6.60%), and 2.40% (95% Cl: 1.43%, 3.37%) in daily outpatient-visits for HPV infections, respectively. The association was more significant in those women aged 41 or over. As for 10 μg/m 3 increase of O3, a −1.33% (95% Cl: −2.13%, −0.530%) change was observed on the lag 03 and such effects appeared to be more obvious in the aged 18–40 group. Our results provided the first evidence that short-term exposure to ambient pollutants was related to, which may be indirectly, the increased risk of HPV infections while O3 may act as a "protective" factor. Graphical abstract: Image 1 Highlights: This's the first study to link HPV infection to short-term air pollution exposure. Positive association for PM10, PM2.5, SO2, NO2, CO and negative association for O3 . The association was age-dependent. Our data may shed new light on both the prevention and treatment of HPV infections. Abstract : Short-term ambient air pollution and HPV.